2018
DOI: 10.1002/eap.1670
|View full text |Cite
|
Sign up to set email alerts
|

Grazing alters net ecosystem C fluxes and the global warming potential of a subtropical pasture

Abstract: The impact of grazing on C fluxes from pastures in subtropical and tropical regions and on the environment is uncertain, although these systems account for a substantial portion of global C storage. We investigated how cattle grazing influences net ecosystem CO and CH exchange in subtropical pastures using the eddy covariance technique. Measurements were made over several wet-dry seasonal cycles in a grazed pasture, and in an adjacent pasture during the first three years of grazer exclusion. Grazing increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 124 publications
(241 reference statements)
3
30
0
3
Order By: Relevance
“…Previous research has shown that changes in soil hydrology can increase, decrease, or have no effect on R eco . Consistent with our results, Jimenez et al () found that increased water table decreased R eco of a tropical herbaceous wetland when soil was flooded due to low soil O 2 availability and reduced aerobic decomposition (Gomez‐Casanovas, DeLucia, Bernacchi, et al, ; Lu et al, ). Hirano et al () showed that variations in soil hydrology did not correlate with changes in R eco when factors other than hydrology (e.g., temperature and GPP as in our study) were the dominant factors controlling R eco .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Previous research has shown that changes in soil hydrology can increase, decrease, or have no effect on R eco . Consistent with our results, Jimenez et al () found that increased water table decreased R eco of a tropical herbaceous wetland when soil was flooded due to low soil O 2 availability and reduced aerobic decomposition (Gomez‐Casanovas, DeLucia, Bernacchi, et al, ; Lu et al, ). Hirano et al () showed that variations in soil hydrology did not correlate with changes in R eco when factors other than hydrology (e.g., temperature and GPP as in our study) were the dominant factors controlling R eco .…”
Section: Discussionsupporting
confidence: 91%
“…Average annual precipitation (1980 to 2015) was 1,310 mm, with two thirds of total annual precipitation falling during the wet season (DayMet database; Thornton et al, ). By quantifying the biophysical controls of CO 2 and CH 4 fluxes from a subtropical wetland and the direct and indirect influence of these controls on C fluxes by combining high‐resolution greenhouse gas (GHG) data with structural equation modeling, this study complements previous work from MAERC that investigated the effect of grazing on C fluxes of subtropical pastures (Gomez‐Casanovas, DeLucia, Bernacchi, et al, ; Gomez‐Casanovas, DeLucia, Bernacchi, et al, ) and the effect of water management (Chamberlain et al, , ) on CH 4 emissions from a subtropical pasture monoculture. Other studies in the area include Chamberlain et al () that investigated the contribution of CH 4 emissions from ruminant fermentation to CH 4 fluxes in a wetland‐pasture landscape mosaic and DeLucia et al () that evaluated the impact of surrounding land use on CH 4 emissions from subtropical wetlands.…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations